Automated target controlled anaesthesia injector - Vidhya Lakshmi.S, Sri; Luxcy.E, Andrews; U, Vishnupriya; Haripriya.A, Bhargavi (International Journal of Engineering and Technology, 2018)
Anaesthesia plays a vital role in major operations which lasts for longer duration of time. The anaesthetic condition of a patient is determined by an anaesthetist based on the body conditions and feed the amount of anaesthesia to be delivered into a modern anaesthesia machine, which delivers the drug as instructed. If a patient experience a sudden change in the body condition where the instructed anaesthesia level cannot help, the anaesthetist and doctors will face severe problems during the operation which leads to patient awakening or may even cause death. So, the patient’s body condition has to be continuously monitored and the anaesthesia dosage has to be delivered based on the changes in the body condition. This requires an automated operation of anaesthesia injector which works based on the changes in the patient’s body condition by monitoring the vital parameters by itself. This can avoid over dosage and its side effects, eventually reduces the death rate caused by the improper administration of Anaesthesia.Initially, certain amount of dosage is delivered by the anaesthetist based on the patient’s condition and earlier reports. Then, during the surgery the anaesthesia is administered if required by this ‘Automated Target Controlled Anaesthesia Injector’. Our idea is to monitor the necessary body parameters like temperature, blood pressure, and heart rate by the sensors interfacing it to the microcontroller-PIC16f877a and programmed to deliver the dosage level using stepper motor based on the changes in the parameters. Though, there are so many ideas on automated operation of anaesthesia injector using different micro-controllers and microprocessor, the revolution made in this idea is to use PIC Microcontroller which has an advantage of in-built amplifier, analog to digital convertor & EEPROM coupling with the vital parameters determining the dosage to be administered and assistive mobile-app which helps to reduce the work of anaesthetist by monitoring even from distant places.